Effect of lime on the physical, mechanical, and hydration properties of circulating fluidized bed fly ash-blast furnace slag-based cementitious materials - Jinzhuang Lv; Xingyi Wang; Jingchao Yang; Bin He; Xiaoyuan Wang; Pengju Han (Case Studies in Construction Materials, 2024)
Lime is a widely used construction and building material. As an alkali activator, lime can reduce costs, improve safety of on-site construction, and ensure environmental benefits. In this study, the effects of different lime contents on the physicomechanical characteristics and the hydration properties of circulating fluidized bed fly ash-blast furnace slag-based cementitious materials (CBCM) were evaluated. The results revealed that flowability and setting time of CBCM decreased with the increasing lime content. The mechanical properties first showed an increasing trend and then declined, achieving their optimal levels at 20 % lime content. Similar to the mechanical properties, the density of CBCM increased first and then decreased with the increase of lime content, enriching its maximum at the same lime amount. The main hydration products of CBCM are ettringite and C-(A)-S-H gel. Ettringite is mainly generated in large quantities within 3 days, which is the main reason for the early strength of CBCM. The highest reaction degree of calcium hydroxide was obtained at the lime content of 20 %, and a significant amount of dense foil-like C-(A)-S-H gel was formed. The calcium hydroxide precipitated once the lime content exceeded 20 %. The hydration reaction was blocked, and the hydration products were relatively reduced.